Protocol for the use of an Optical Nitrate Nitrogen (NO3N) sensor for measuring ground and surface water NO3N concentrations - Justin Legg; Sarah M. Mager; Sophie L. Horton (MethodsX, 2025)
Optical nitrate-nitrogen (NO3N) sensors are used in environmental monitoring for the real-time detection of dissolved inorganic nitrate and are readily available and increasingly affordable for use by non-experts and may eventually replace the need for expensive laboratory analysis. Many different manufacturers have developed their own instruments for use as permanent in situ sensors in groundwater bores, or as portable ex situ units. The advantage of these NO3N sensors is that they can be deployed to complement traditional discrete sampling programmes and significantly improve temporal data resolution and provide high resolution data that captures the rate that NO3N may naturally vary in the environment. However, the potential over dependence on technology i.e. a plug and play approach without careful development of quality assurance protocols can easily lead to poor data outcomes. Thus, the effective use of an optical NO3N sensor, especially in community-led science, requires specific sensor protocols for its effective use, including: • A regimen of cross checks relative to known standards and/or independently verified laboratory results; • the collection of metadata to contextualise the results; and, • the need for Quality Assurance and Quality Control (QAQC) protocols to provide confidence in the data.